COVID‐19 and the Canadian cattle/beef sector: Some preliminary analysis. (27th June 2020) - Rude, James
Abstract: Canada's cattle/beef sector has already weathered a shock after a 2003 case of BSE resulted in closed borders and industry restructuring. Now, the sector has to adjust to similar shocks due to COVID‐19. This paper examines the supply chain from the consumer up to the cow–calf producer by considering consumer reactions, labor market constraints, and supply response. A quarterly market model of North American cattle and beef markets is used to examine price and revenue impacts associated with the market disruptions. Depending on the scenario, there is considerable price and revenue suppression at all levels of the market. Abstrait: Le secteur canadien du bœuf a déjà subi un choc après qu'un cas d'ESB en 2003 eut entraîné la fermeture des frontières et la restructuration de l'industrie. Maintenant, le secteur doit s'adapter à des chocs similaires dus au COVID‐19. Cet article examine la chaîne d'approvisionnement du consommateur au producteur de vache‐veau en tenant compte des réactions des consommateurs, des contraintes du marché du travail et de la réponse de l'offre. Un modèle de marché trimestriel des marchés nord‐américains du bœuf est utilisé pour examiner les effets sur les prix et les revenus associés aux perturbations du marché. Selon le scénario, il y a une compression considérable des prix et des revenus à tous les niveaux du marché.